EVALUASI PROGRAM LAYANAN PENGADUAN DIGITAL PERUNDUNGAN SISWA DI DENPASAR - Yani, Erna; Patimah, Siti; Saputra, M. Indra; Warisno, Andi; Putri, Ni Putu Laksmi Resti (Ibn Khaldun University, Bogor, 2025)
This study evaluates the anti-bullying digital complaint service program